French and German support to Portugal: The military survival of the «Estado Novo» (1958-1968) - Fonseca, A. M.; Marcos, D. (Portuguese Studies Review, 2008)
When the colonial wars erupted in Angola in 1961, Salazar’s regime was already preparing the military reaction to the nationalist movements. In this article, we will show how the diplomatic and political manoeuvres allowed Portugal to embrace in a colonial war that would last for thirteen years, fought in three different territories. Forced by the anti-colonialism of the United States to seek for new supports, the Estado Novo turned itself into the European powers, France and the Federal Republic of Germany, to obtain the military equipment it needed. This represented a major change in the foreign policy strategy of Portugal. Without this successful diplomatic effort, the Portuguese Armed Forces would never have the minimum conditions to fight the Colonial Wars.